2007
DOI: 10.1152/physiol.00011.2007
|View full text |Cite
|
Sign up to set email alerts
|

Facilitated Hexose Transporters: New Perspectives on Form and Function

Abstract: The recent sequencing of the human genome has resulted in the addition of nine new hGLUT isoforms to the SLC2A family, many of which have widely varying substrate specificity, kinetic behavior, and tissue distribution. This review examines some new hypotheses related to the structure and function of these proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
205
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(208 citation statements)
references
References 56 publications
(62 reference statements)
1
205
0
Order By: Relevance
“…81 for review). In the original studies, GLUT3 was consistently found to exhibit a lower K m than its other Class 1 counterparts, GLUT1, -2, and -4, with K m values for 2-deoxyglucose uptake of 1.4 mM compared with GLUT1, 6.9 mM, GLUT2, 11.2 mM, and GLUT4, 4.6 mM; K m values for 3-O-methylglucose equilibrium exchange of 10.6 compared with K m for GLUT1, -2, and -4 of 21, 42, and 4.5 mM, respectively (6,46,47,63,81,96). GLUT3 was also shown to transport mannose, galactose, and xylose but is unable to transport fructose.…”
Section: Kineticsmentioning
confidence: 94%
See 1 more Smart Citation
“…81 for review). In the original studies, GLUT3 was consistently found to exhibit a lower K m than its other Class 1 counterparts, GLUT1, -2, and -4, with K m values for 2-deoxyglucose uptake of 1.4 mM compared with GLUT1, 6.9 mM, GLUT2, 11.2 mM, and GLUT4, 4.6 mM; K m values for 3-O-methylglucose equilibrium exchange of 10.6 compared with K m for GLUT1, -2, and -4 of 21, 42, and 4.5 mM, respectively (6,46,47,63,81,96). GLUT3 was also shown to transport mannose, galactose, and xylose but is unable to transport fructose.…”
Section: Kineticsmentioning
confidence: 94%
“…Together with GLUT1, -2, and -4, it comprises the Class 1 group of transporters (For review see Refs. 15,81,121). With the cloning of GLUT3, it became apparent that the brain did not rely exclusively on GLUT1 and that GLUT3 was highly and specifically expressed by neurons.…”
mentioning
confidence: 99%
“…The glycogen content in a cell depends on the intracellular levels of glucose, which in turn may also be dependent on the glucose transport across the plasma membrane via GLUTs. In fat and muscle cells, GLUT4, a unique insulin-sensitive glucose transporter, is translocated in the presence of insulin from the cell interior to the plasma membrane, enabling glucose entry (67). Astrocytes appear to express GLUT1 and GLUT3 at a high level but very little GLUT2 and GLUT4 (27).…”
Section: Insulin and Igf-1 Increase Glycogen Content In Astrocytes Inmentioning
confidence: 99%
“…The glucose transporter (GluT) protein family consists of 14 members grouped into three major classes based on sequence homology and substrate selectivity (8). GluT proteins mediate the transport of glucose and other monosaccharides into and out of mammalian cells according to a concentration gradient (9).…”
Section: Introductionmentioning
confidence: 99%
“…oncogenes and growth factors are responsible for GluT overexpression in malignant cells (8). increase in glucose transport and metabolism may reflect an adaptative requirement by these rapidly growing cells for more sources of energy (11).…”
Section: Introductionmentioning
confidence: 99%